Economic Order Quantity Method to Enhance Rice Supplies and Food Security in Indonesia - Liperda, Rahmad Inca; Ruswandi, Nanda; Apriliani, Dea Nurfirda (Institut Transportasi dan Logistik Trisakti, 2024)
Ensuring adequate food provision to meet human basic needs is of utmost importance. In Indonesia, achieving food security involves meeting the food requirements of all individuals and eliminating the risk of famine. The government's strategy to ensure national food security centers on maintaining a steady supply of rice throughout the year, recognizing its paramount significance. To address this concern, this study aims to enhance rice supplies at Gudang Bulog Baru Tempel Lemahbang 202 Blora by implementing the economic order quantity (EOQ) method. The research findings demonstrate that by utilizing the EOQ method, the optimal rice supply order size would be 15,319.4 tons. This order should be placed 119 times per year, given the 280 business days available. The annual cost of implementing this policy at Gudang Bulog Baru Tempel Lemahbang 202 Blora is estimated to be Rp. 424,484,526. Implementing the EOQ method proves beneficial in minimizing the cost for individual rice orders due to its high frequency throughout the year, which directly affects the total cost. Nevertheless, it is crucial to reassess alternative policies to further reduce the overall cost incurred in both the short and long term if the objective of the EOQ method is cost minimization.Top of Form